Seagrass in a Changing Estuary, the Indian River Lagoon, Florida, United States - Morris, Lori J.; Hall, Lauren M.; Jacoby, Charles A.; Chamberlain, Robert H.; Hanisak, M. Dennis; Miller, Janice D.; Virnstein, Robert W. (Frontiers in Marine Science, 2022)
Seagrass is a major structural habitat in the Indian River Lagoon. Maps documented locations and areal extents of beds periodically since the 1940s, and surveys of fixed transects yielded changes in percent cover and depths at the end of the canopy since 1994. Areal extent increased by 7,000 ha from 1994 to 2009, mean percent cover within beds decreased from 40% to 20%, and mean percent cover standardized to maximum transect length remained near 20%. Thus, conditions supported a consistent biomass because cover decreased as areal extent increased. Between 2011 and 2019, 19,000 ha or 58% of seagrasses were lost, with offshore ends of canopies moving shoreward and shallower, and standardized mean percent cover decreased to 4%. These changes coincided with blooms of phytoplankton, and  27% of incident subsurface irradiance at 0.9 m was stressful. Decreases in mean percent cover per month of stress became larger when initial mean cover per transect was < 20%, which suggested that the ratio of aboveground to belowground tissues in the expanded and sparser beds led to respiratory demand that was not met by photosynthesis. Despite intermittent improvements in light penetration, widespread recovery of seagrasses has not occurred potentially due to detrimental feedbacks. For example, loss of seagrass exposed sediments to waves, and the resulting disturbance may have hampered recruitment of new shoots. The same decreases also made 58%–88% of the carbon, nitrogen, and phosphorus in seagrass tissue available to other primary producers. These nutrients did not enhance growth of epiphytes, whose biomass decreased by 42%, but they apparently fueled blooms of phytoplankton, with mean chlorophyll-a concentrations increasing by > 900%. Such intense blooms increased shading and loss of seagrasses. Fortunately, data showed that patches of seagrasses at depths of 0.5–0.9 m persisted for 22–24 years, which suggested that this depth zone could hold the key to recovery. Nevertheless, optimistic estimates predict recovery could take 12–17 years. Such a long-term, widespread loss of a key structural habitat may generate multiple adverse effects in the system, and mitigating such effects may entail planting seagrasses to accelerate recovery.